MORPHOLOGICAL FEATURES OF THE ANATOMY OF TEMPORARY AND PERMANENT TEETH - Malika Ilkhomovna Kamalova; Kosimov Sardor Abdullo Ugli; Amonova Zilola Kakhramonovna; Khamrakulov Zhakhongir Ulmasovich; Ashurmatov Muhammadamin Alijon Ugli (Western European Studies, 2023)
The permanent tooth has the largest diameter at the equator. Baby teeth have thinner hard tissue due to their reduced mineralisation. Permanent teeth are more mineralised, so their hard tissue is thicker. The cavity of a deciduous tooth is more extensive than that of a permanent tooth
Keywords: permanent and deciduous teeth; morphological features